Analisis Faktor Pendukung dan Penghambat Komunitas Bank Sampah Induk New Normal serta Solidaritas Penggiat Lingkungan dalam Penguatan Kewarganegaraan Ekologis Medan - Agung Torang Sitohang; Fazli Rachman (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Environmental problems in the city of Medan, such as high garbage piles, air and water pollution, and limited green open spaces, have become serious challenges that demand direct involvement from residents and local communities. Environmental management efforts cannot fully rely on the government, but require active collaboration from various parties, including environmental care communities. This study aims to analyze the supporting and inhibiting factors faced by communities in strengthening ecological citizenship, focusing on the study of the New Normal Main Waste Bank and the Environmental Activist Solidarity Community in Medan City. The research approach uses a descriptive qualitative method with data collection techniques through semi-structured interviews, non-participant observations, and documentation of community activities. The results of the study show that the main driving factors include the availability of waste management facilities and tools, harmonious social relations, ease of activity methods, and personal motivation of members. In addition, family values, openness of participation, and positive feedback from the community strengthen the collective spirit of the community in driving ecological action. On the other hand, the community faces various obstacles, such as limited time and manpower, low public awareness of environmental issues, ecological knowledge gap, and lack of regulatory and funding support. These factors often slow down collective efforts to achieve sustainability targets. The findings of the study confirm that the success of community action depends not only on the availability of resources, but also on social resilience, consistency of shared values, and adaptability to structural challenges. Therefore, this study recommends the importance of strengthening institutional support, building the capacity of human resources, and sustainable education campaigns to encourage active and sustainable citizen participation in protecting the environment.